2020
DOI: 10.1021/acs.inorgchem.0c02205
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Lability Driven by Metal-to-Borane Pseudorotation: A Mechanism for Ligand Exchange

Abstract: The discovery of systems that interact with small molecules plays a vital facilitating role in the development of devices that show sensitivity to their surroundings and an ability to quickly relay chemical and physical information. Herein, we report on the reaction of [NiCl 2 (dppe)] with decaborane that produces in usable yield a new 11-vertex nickelaborane, [7,7-(dppe)-nido-7-NiB 10 H 12 ] (1), which shows interesting reactivity and functionality toward carbon monoxide and ethylisonitrile. This contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[56][57][58][59][60][61][62][63] We have recently reported that metal-to-borane rotation can have an effect on the lability of the metal-bound exo-polyhedral ligands, and hence the opening of coordination sites for ligand substitutions. 64 The isomerization of the metal exo-ligand symmetric conformer in ortho-cyclometallated [6-H-6-(PPh 3 )--6 P ,5 C -(PPh 2 -ortho-C 6 H 4 )nido-6-IrB 9 H 12 ] to its asymmetric isomer, 65 suggests that rotation of the metal vertex with respect to the { 3 -B 9 H 13 } fragment in 1, 2, 3 and 4 is a feature worthy of study. We therefore modelled the rotation of the exo-polyhedral ligand sphere by performing a DFT-calculated relaxed Potential Energy Surface (PES) scan of the system, in which the PPh 3 ligands are replaced by PH 3 in order to save computational time.…”
Section: Articlementioning
confidence: 99%
“…[56][57][58][59][60][61][62][63] We have recently reported that metal-to-borane rotation can have an effect on the lability of the metal-bound exo-polyhedral ligands, and hence the opening of coordination sites for ligand substitutions. 64 The isomerization of the metal exo-ligand symmetric conformer in ortho-cyclometallated [6-H-6-(PPh 3 )--6 P ,5 C -(PPh 2 -ortho-C 6 H 4 )nido-6-IrB 9 H 12 ] to its asymmetric isomer, 65 suggests that rotation of the metal vertex with respect to the { 3 -B 9 H 13 } fragment in 1, 2, 3 and 4 is a feature worthy of study. We therefore modelled the rotation of the exo-polyhedral ligand sphere by performing a DFT-calculated relaxed Potential Energy Surface (PES) scan of the system, in which the PPh 3 ligands are replaced by PH 3 in order to save computational time.…”
Section: Articlementioning
confidence: 99%
“…1–3 While enthalpy favours ML bond formation, entropy drives their dissociation such that all ML bonds exist to varying degrees in dynamic equilibria between bound and unbound states. This bond lability impacts the mechanisms of transition metal catalysis 4–6 and enables the self-healing behaviour observed in coordination polymers. 7–10 Among traditional solid-state materials, the earliest examples of ferroelectric phase-change behaviour were documented to involve a special class of ML phonons, 11–13 now termed soft modes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] While enthalpy favours ML bond formation, entropy drives their dissociation such that all ML bonds exist to varying degrees in dynamic equilibria between bound and unbound states. This bond lability impacts the mechanisms of transition metal catalysis [4][5][6] and enables the self-healing behaviour observed in coordination polymers. [7][8][9][10] Among traditional solid-state materials, the earliest examples of ferroelectric phase-change behaviour were documented to involve a special class of ML phonons, [11][12][13] now termed soft modes.…”
mentioning
confidence: 99%